ESENSI TEORI BEHAVIORISME DAN PANDANGANNYA TERHADAP MEDIA DAN TEKNOLOGI PEMBELAJARAN SERTA RELEVANSINYA DALAM PENDIDIKAN ISLAM - Saridudin (Program Studi Pendidikan Agama Islam, 2023)
The behaviorist school of thought emphasizes the principle of stimulus and response as a change in behavior. In determining several education policies in Indonesia, this behaviorist ideology still dominates, especially in policies that are fundamental and principled, as seen especially in the 2003 National Education System Law. For this reason, behaviorist education policies need to look at the reality on the ground and take an approach innovative in the learning process, including alignment in Islamic education. However, the readiness of various elements of the education system is the determining factor. Therefore, educational policies that are relevant to the demands of change must be supported by all educational actors, including other educational components. This article discusses various things regarding behaviorism, including the theory of behaviorism according to several figures; the main characteristics of behavioristic theory and its learning principles; the concept of reward and fun in behaviorist learning theory; the relevance of behaviorism learning theory to Islamic education; the role of media and technology in Behavioristic Learning; the dominance of the behavioristic approach in the formulation of education policy in Indonesia and several criticisms expressed against the behaviorist school